The carbon deposits formed by reaction of a series of red mud samples with methanol. Issue 52 (11th May 2016) - Gu, Hannian; Hargreaves, Justin S. J.; McFarlane, Andrew R.; MacKinnon, Gillian
Abstract : Magnetic carbon materials were prepared by the catalytic growth of graphitic carbon and carbon nanofibers using methanol as carbon source with a series of red mud wastes from different sources. Abstract : Magnetic carbon materials were prepared by the catalytic growth of graphitic carbon and carbon nanofibers using methanol as a carbon source with a series of different red mud wastes. Both the raw red mud samples and the products were characterized using powder X-ray diffraction, scanning electron microscopy, Raman spectroscopy, Brunaeur Emmett and Teller surface area analysis, thermogravimetric analysis and carbon content analysis. Hematite and goethite in high iron content red muds were reduced into magnetite in 10 minutes at 500 °C, and graphitic carbon reflections were evident in the resultant powder X-ray diffraction pattern. Thus, the samples become magnetic and change color from red to black. After six hours reaction at 500 °C, the carbon content of the composite based on a high iron content Bayer process derived red mud reached as high as ca. 72% and its surface area increased from 17 to 312 m 2 g −1 .